New Geographical Record of Three-Spine Frogfish, Batrachomoeus Trispinosus (Günther 1861) From the River Rupsa, Bangladesh - Ahmed, Md Sagir; Datta, Sujan Kumar; Saha, Tonmoy; Zhilik, Ayesha Akhter; Chowdhury, Nishat Zahan; Ahmed, Sumaiya (Bangladesh Journal of Zoology, 2020)
Abstract Not Available Bangladesh J. Zool. 48(1): 197-202, 2020